Estudo computacional da difusão de água em nanotubos de carbono induzida por gradiente de pressão - Segatto, Carla Adriane Ramos (2013)
In this work we present a computational study of the properties of water transport across membranes formed of carbon nanotubes (CNT) armchair with different diameters, when subjected to pressure gradients 80-400 MPa. This study was made through the implementation of the method of molecular dynamics code NAMD. The model adopted for our simulation consists of a unit cell containing water molecules that will cross through the reverse osmosis process, 9 carbon nanotubes 20Å in length, using the periodic boundary conditions. The results show a quadratic dependence of the flow on the diameter of the nanotubes. CNT in smaller diameters, the dependence of the flow on the pressure applied is small. This behavior differs for larger diameter nanotubes, where the flow increases linearly with pressure. When analyzing the mean square displacement (MSD) as a function of the diameter of the CNT, we found the occurrence of a regime of ballistic diffusion for all cases. The effect of CNT on the diameter of MSD for the same pressure gradient indicates differences between the coefficients of diffusion of the bulk water and CNT. We found evidence of the occurrence of a non-Fickian transport for this condition of confinement. The analysis flow of water molecules suggests that the CNT membranes can apparently be competitive systems with existing techniques and used on the market for water purification.